Code-switching and Code Mixing on Vlog: A Sociolinguistics Study - Emma Asyirotul Umami; Betari Irma Ghasani (Institut Agama Islam Negeri Salatiga, 2021)
This paper aims for identifying the type of codeswitching and codemixing found on the vlog and recognizing factors causing codeswitching and codemixing. The researchers take data from 14 vlogs of Nurul Taufik themed Jaamiah or Campus. Some steps done in doing the research including listening to the vlog, analysing, and reporting. The result shows that there are 20 data of codeswitching and 52 data of codemixing. All forms of codeswitching belong to extraneous in the form of sentences. Some factors causing code switching are including speakers, interlocutors, the presence of a third person and changes in the topic of discussion. In addition, the form of code mixing is extraneous codes in the form of words, phrases, baster, repetition of words, expressions, and clauses. The cause of codemixing is the speaker's desire to get the “right” expression, and the habits and relaxedness of the speech act participants in communicating.